2022
DOI: 10.7241/ourd.20222.32
|View full text |Cite
|
Sign up to set email alerts
|

Unilateral bullous pemphigoid in a hemiplegic patient

Abstract: Sir, Bullous pemphigoid (BP) is the most common autoimmune bullous dermatosis, mainly affecting the elderly. Its association with neurological diseases has been reported for several years in several studies, including with strokes. We report a new case of unilateral BP in a hemiplegic patient. A 78-year-old patient with a history of hypertensive and ischemic heart disease and ischemic stroke three years ago was admitted for pruriginous bullous dermatosis evolving for one month prior to admission. A general … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…The pathogenesis of BP remains not established with concrete evidence. Some studies have shown that BP has a correlation with co-morbid conditions such as neurological and psychiatric diseases, diabetes mellitus, and malignancies [2][3][4]. Recently, it has also been observed that the incidence of BP has raised, which could be attributed to factors such as an aging population, an increase in drug-induced cases, and the ameliorated diagnosis of the non-bullous forms [5].…”
Section: Introductionmentioning
confidence: 99%
“…The pathogenesis of BP remains not established with concrete evidence. Some studies have shown that BP has a correlation with co-morbid conditions such as neurological and psychiatric diseases, diabetes mellitus, and malignancies [2][3][4]. Recently, it has also been observed that the incidence of BP has raised, which could be attributed to factors such as an aging population, an increase in drug-induced cases, and the ameliorated diagnosis of the non-bullous forms [5].…”
Section: Introductionmentioning
confidence: 99%